2016
DOI: 10.1038/srep20358
|View full text |Cite
|
Sign up to set email alerts
|

Circulating and tumor-infiltrating mucosal associated invariant T (MAIT) cells in colorectal cancer patients

Abstract: Mucosal associated invariant T (MAIT) cells are important for immune defense against infectiousMucosal associated invariant T (MAIT) cells are innate-like T cells expressing a semi-invariant T cell receptor (TCR) of Vα 7.2-Jα 33 chain and a limited array of Vβ 2 or Vβ 13 chain in humans 1 . Circulating and tissue-infiltrating MAIT cells can be characterized by expressing Vα 7.2 segment with either CD161 or IL-18Rα on cell surface 2,3 . MAIT cells are preferably resident in the intestinal mucosa and liver in hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
185
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(207 citation statements)
references
References 47 publications
20
185
2
Order By: Relevance
“…In the present study, MAIT cells were found to be more accumulated in colon cancer tissue than in the unaffected tissue, consistent with previous studies [14, 34]. Circulating MAIT cells have been reported to preferentially express CCR6, supporting their migration to the intestine [9].…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, MAIT cells were found to be more accumulated in colon cancer tissue than in the unaffected tissue, consistent with previous studies [14, 34]. Circulating MAIT cells have been reported to preferentially express CCR6, supporting their migration to the intestine [9].…”
Section: Discussionsupporting
confidence: 92%
“…While higher frequencies of IL-17-producing cells have been reported in colorectal tumors, [9][10][11][12]14 to our knowledge this is the first time that enhanced cytokine production per cell by inflammatory T cells infiltrating the CRC TME has been reported. The TME has high levels of cytokines that boost inflammatory T cell differentiation and function such as IL-6.…”
Section: Discussionmentioning
confidence: 93%
“…We and others have shown a higher frequency of IL-17-producing T cell populations, including MAIT cells and gd T cells, in tumor versus adjacent bowel tissue. [9][10][11][12][13][14] Differences in the frequency of regulatory T cells (Tregs) have also been observed, 10,11 but the effect of the function of these T cell populations on other infiltrating T cells is not clear. We hypothesized that T cells in tumor tissue would have impaired cytokine production and proliferative ability due to the suppressive environment in CRC tumors.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study, conducted on advanced human colorectal cancer (CRC) tissues showed, a significant higher frequency of MDR1 + CD161 + T cells, considered mostly as MAIT cells by the authors, in the tumor tissue compared to adjacent healthy tissues. 100 In this matter, evaluation of MDR1 expression by immune subtypes should be more extensively investigated. The hostile tumor micro-environment and its chemical composition must indeed shape the immune infiltrate, and MDR1 expression by anti-tumor immune cells may favor their preservation despite harsh environmental conditions.…”
Section: Introductionmentioning
confidence: 99%